ANALISIS TINGKAT KETERAMPILAN BERBICARA SISWA PADA PROGRAM GEMBIRA DONG DI SDN 94 SINGKAWANG - Lusiana, Lusiana; Wijaya, Andika Kusuma; Oktavia, Wahyuni (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to analyze the level of students’ speaking skills in the Gembira Dong program at SDN 94 Singkawang. The research employed a quantitative approach with a descriptive design. Data were collected through a speaking test administered to 28 representative students and analyzed descriptively. The results showed that the speaking skills of fourth-grade students at SDN 94 Singkawang were generally in the good category across all assessed aspects. The percentage scores for each aspect were as follows: pronunciation 66%, intonation 65%, fluency 67%, language use and content 79%, and expression 66%. The overall average score across these five aspects was 69%, indicating a good level of speaking proficiency. Therefore, it can be concluded that the students’ speaking skills in the Gembira Dong program at SDN 94 Singkawang are categorized as good.